Energy analysis of broiler chicken production system with darkhouse installation - Matheus C. Mattioli; Alessandro T. Campos; Tadayuki Yanagi Junior; Diego B. Marin; Tony M. C. Eugênio; José E. V. Costa Junior (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the sustainability of a broiler chicken production system, with confinement in Darkhouse sheds, by energetic analysis. Energy flows of a complete production cycle, 56 days, were considered, of which the energy inputs and outputs were computed in direct and indirect forms, by estimating the energy coming from the quantity of feed, water, machinery and equipment, human labor, sheds, silos, among other components of the productive system, multiplied by their respective energetic coefficients. The total energy demand of a system in a production cycle for the production of 1 kg of live chicken and its energy efficiency coefficient were determined. The studied system had energy conversion coefficient of 95%, demonstrating that the production model has high energy conversion efficiency and fits a sustainable model. On average, 37.55 MJ kg-1 of live chicken were necessary. The main limiting point of the system corresponded to the energy consumed in the form of feed, with 75% of the total direct energy.